Physician assistant/associate career flexibility: factors associated with specialty transitions - Andrzej Kozikowski; Mirela Bruza-Augatis; Dawn Morton-Rias; Kasey Puckett; Colette Jeffery; James F. Cawley; Roderick S. Hooker; Alicia Quella; Sheila Mauldin; Joshua Goodman (BMC Health Services Research, 2024)
Abstract Background Physician assistants/associates (PAs), due to their broad medical education and certification, have the flexibility to change specialties throughout their careers. Prior studies suggest that between half and three-quarters exercise this option at some point in their career, and a third do so within the first decade. However, more research is needed to understand the factors associated with PAs changing vs. remaining in the same specialty throughout their professional journey. Methods A cross-sectional analysis using a 2023 national dataset was conducted to examine specialty transitions throughout PAs' careers. We analyzed responses (N = 121,947 [81.3% response rate]) to a question asking how many times PAs changed specialties throughout their careers. Our investigation included specialty changes overall and separately within career-stage subgroups. We also explored demographics and practice attributes associated with specialty change patterns. Results Most PAs change specialties at least once during their careers, with some making this transition as many as six or more times. The highest proportion of change occurs in the first, followed by the second decade of practice. In the first 10 years, 40.3% of PAs changed specialties. In multivariate analysis, duration of practice was the strongest factor associated with increased odds of transitioning. PAs practicing for 31 or more years had over four-fold higher odds of changing specialties than PAs practicing for 10 or fewer years. Other factors strongly linked to specialty changes included working in critical care medicine or psychiatry, holding two or more clinical positions, practicing in urgent care, being an independent contractor, female gender, serving in the military, and possessing a doctorate. The pattern of significant PA characteristics linked with specialty changes was largely consistent when comparing the overall cross-sectional analysis with separate subgroups of PAs within different career stages. Conclusion PAs exhibit a high degree of career flexibility when it comes to changing specialties. Our research demonstrates that by the late-career stage, three-fourths of PAs have transitioned between at least two disciplines; however, most changes occurred in the first decade of practice. This study further substantiates the PA profession's attributes, highlighting its unique characteristics, such as its adaptability and capacity for career flexibility.